Contractibility of Fixed Point Sets of Mean-Type Mappings. (31st December 2017) - Iampiboonvatana, S.; Chaoha, P.
Abstract : We establish a convergence theorem and explore fixed point sets of certain continuous quasi-nonexpansive mean-type mappings in general normed linear spaces. We not only extend previous works by Matkowski to general normed linear spaces, but also obtain a new result on the structure of fixed point sets of quasi-nonexpansive mappings in a nonstrictly convex setting.